Stand-alone backup power system for electrical appliances with solar PV and grid options - Sabre, A. H.; Wan Hasan, Wan Zuha; Nordin, Farah Hani; Ab Kadir, Mohd Zainal Abidin (Institute of Advanced Engineering and Science, 2020)
For a portable backup power system, there is an essential need to contribute to increasing the energy conversion efficiency between the source and the electrical household appliances to overcome the recent issues of global warming. This paper proposes a Backup power system (BPS) compatible with the capability to match with two primary power sources; Grid-Connected power as an AC and solar-PV as a DC power source. This system composes of a rechargeable battery bank of about 300V, while the voltage matching concept keeps maintaining the battery fully charged as long as the source power is available. Matlab-based simulation has performed to prove the concept of the adopted voltage-matching. A relay switch circuit controlled by the main power source is used to change-over the load/appliances between direct link through bypassing the main power and the storage battery power when both options of main power are unavailable. The result shows the excellent utilization of the traditional BPS losses, the proposed topology can achieve about 99% power efficiency as compared with the traditional one.